EP637 Are any pathologic variables of lymph node metastases reliable enough to predict survival in high grade endometrial cancer?. (1st November 2019) - Ntzeros, K; Thomakos, N; Sotiropoulou, M; Dimopoulou, S; Vlachos, DE; Haidopoulos, D; Liontos, M; Bamias, A; Rodolakis, A
Abstract : Introduction/Background: Specific pathologic characteristics of nodal metastases may have prognostic implications on their own. The aim of this study is to identify whether pathologic characteristics of pelvic and para-aortic nodal metastases in high grade endometrial carcinomas affect recurrence and survival. Methodology: We conducted a retrospective study of patients with stage IIIC1 and IIIC2 high grade endometrial carcinomas (endometrioid, serous and clear cell type) from 2005 to 2012, evaluating the size of lymph node metastases (≤10 mm or >10 mm), number (≥1) and location (pelvic or para-aortic) of lymph nodes involved, duration of follow-up and length of time to recurrence. Cox regression analysis was used. Results: The study included 68 women with mean age 61.9 years. Thirty were classified as high grade endometrioid, 24 serous and 14 clear cell. Fifty patients had Stage IIIC1 disease and the remaining IIIC2. The mean follow up period was 4.5 years. 52.9% of the patients had a recurrence. Twenty four patients (35.3%) died during the follow up. Advanced local disease as indicated by cervical stroma invasion and adnexa involvement were associated with greater hazard for recurrence (HR=2.83, 95% CI: 1.09–7.32, p=0.032 and HR=3.13, 95% CI: 1.24–7.94, p=0.016 respectively). Cervical Involvement was also associated with worse survival (HR=7.40, 95% CI: 1.57–34.84, p=0.011). The pathologic characteristic related with negative prognostic implications was the presence of metastases in >1 lymph nodes. It was associated with greater hazard for recurrence (HR=2.89, 95% CI: 1.10–8.01, p=0.025) and worse survival (HR=3.50, 95% CI: 1.41–18.72, p=0.014). The other variables were not statistically associated with recurrence or survival. Conclusion: In patients with high grade endometrial carcinomas where >1 lymph nodes involved with metastases, were associated with poorer prognosis. In contrary, size and location of lymph node metastases did not affect survival or recurrence. Disclosure: Nothing to disclose.